Henry Miller Travels in Greece. - Sotiropoulos, Leonidas (Journeys, 2017)
Through an examination of Henry Miller’s account of his journey to Greece in 1939, as expressed in his travel book The Colossus of Maroussi, this article examines the image of this country his writing presents. Miller’s description of people, places, and environment is infused with a mystical, spiritual element, as if something magical emanates from the cultural environment of this country and tints the landscape and its inhabitants, adding an atemporal dreamlike quality. The group of literati Miller befriended during his five-month stay in Greece viewed Greek art, culture, and history in an archetypal way, which blends well with Miller’s approach. This analysis of the enchanted world Miller claims to have met and experienced during his journey could thus possibly acquire further significance through tentatively relating it to the way contemporary Greeks may experience aspects of their culture and their Greekness.